The Evolution of the Wage Elasticity of Labor Supply over Time - Todd E. Elder; Steven J. Haider; Cody Orr (Institute of Labor Economics (IZA), 2023)
The uncompensated wage elasticity of labor supply is a fundamental parameter in economics. Despite its central role, very few papers have studied directly how it has changed over time. We examine the evolution of the uncompensated labor supply elasticity using cross-sectional methods over the last four decades. We find robust evidence that the elasticities weakly increased between 2000 and 2020, which represents a striking reversal from the sizeable declines for single and married women between 1979 and 2000. We additionally find that these changes arose almost entirely on the extensive margin. We then conduct a series of counterfactual simulations to identify which factors are most responsible for these trends.
Keywords: D10; J22; 330; labor supply; discrete choice models